PHYLOGENETIC ANALYSIS OF NP AND HN GENE OF NEWLY ISOLATED NDV/Badung-02/AK/14 - Ferbian Milas Siswanto; Anak Agung Ayu Mirah Adi (Jurnal Kedokteran Hewan, 2017)
virus was isolated from suspected Newcastle disease (ND) chicken in backyard farm at Sibang Village, Badung Regency, Bali Province. The isolates were then propagated and confirmed for NDV serologically. RNA isolation was performed by standard Trizol method. Phylogenetic tree analysis of NP gene (nt1020-1561) and HN gene (nt7019-7754) were performed using sequence of Badung-02/AK/14 and selected NDV strains from GenBank. Based on the NP gene sequence, the newly isolate closely related with other NDV strains belong to genotype VII that previously isolated such as Banjarmasin-010/10, Bali-1/07, and Cockatoo/90 with genetic distance 0.2%, 12.6%, and 18.0% respectively. The genetic distance with LaSota/46 virus (genotype II) is 19.6%. Based on HN gene sequence, genetic distance of the Badung-02/AK/14 with other viruses belong to genotype VII such as Banjarmasin-010/10, Bali-1/07, and Cockatoo/90 are 0.4%, 3.7%, and 4.2% respectively. The genetic distance with LaSota/46 virus (genotype II) is 9.0%. There were no difference between the result of nucleotide and amino acid sequence analysis, both in NP and HN gene (P0.05).